2015
DOI: 10.18632/oncotarget.3761
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor activity of selective inhibitors of XPO1/CRM1-mediated nuclear export in diffuse malignant peritoneal mesothelioma: the role of survivin

Abstract: Survivin, which is highly expressed and promotes cell survival in diffuse malignant peritoneal mesothelioma (DMPM), exclusively relies on exportin 1 (XPO1/CRM1) to be shuttled into the cytoplasm and perform its anti-apoptotic function. Here, we explored the efficacy of Selective Inhibitors of Nuclear Export (SINE), KPT-251, KPT-276 and the orally available, clinical stage KPT-330 (selinexor), in DMPM preclinical models. Exposure to SINE induced dose-dependent inhibition of cell growth, cell cycle arrest at G1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 41 publications
(62 reference statements)
4
28
0
Order By: Relevance
“…p53 is an important cargo of CRM1 (45,46), but clearly for EWS, it is not a biomarker to predict response to KPT-330. This appears to be the same in other studies (18,19,(47)(48)(49)(50)(51). For example, in one of our previous studies, we showed that p73 plays an important role in mediating cell cycle EWS cells have very few somatic mutations highlighting the crucial role of the EWS fusion gene and its downstream pathways in the pathogenesis of the disease (3).…”
Section: Discussionsupporting
confidence: 85%
“…p53 is an important cargo of CRM1 (45,46), but clearly for EWS, it is not a biomarker to predict response to KPT-330. This appears to be the same in other studies (18,19,(47)(48)(49)(50)(51). For example, in one of our previous studies, we showed that p73 plays an important role in mediating cell cycle EWS cells have very few somatic mutations highlighting the crucial role of the EWS fusion gene and its downstream pathways in the pathogenesis of the disease (3).…”
Section: Discussionsupporting
confidence: 85%
“…The human mycoplasma-free DMPM cell lines MesoII, STO, MP115, MP4, and MP8 were established in our laboratory [1113]. All cells were cultured in DMEM F-12 medium (Lonza, Milano s.r.l., Treviglio, Italy) supplemented with 10% fetal bovine serum in a 37 °C humidified 5% CO 2 incubator.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the knowledge that several receptor tyrosine kinases (RTKs) are validated targets of miR-34a [8] and our previous results indicating that activation of downstream RTK signaling, in terms of phosphorylation/overexpression of extracellular signal regulated kinase ½ (ERK1/2), AKT, and mTOR, is present in a considerable fraction of DMPM clinical specimens [10], we proposed to investigate the possible relevance of miR-34a in the disease, with the final aim to develop novel therapeutic strategies. Here, we report that miR-34a is down-regulated in DMPM clinical specimens and demonstrate that miR-34a replacement in a unique collection of in-house-developed human DMPM experimental models [1113] inhibits cell proliferation and invasion and impairs tumor growth formation in SCID mice, mainly as a consequence of c-MET and AXL inhibition. These findings identified miR-34a-AXL and -c-MET axes as promising therapeutic targets for DMPM.…”
Section: Introductionmentioning
confidence: 93%
“…As a predominantly cytoplasmic protein, survivin is exported to the cytoplasm through an exclusively XPO1-dependent pathway (5). In malignant peritoneal mesothelioma, survivin was shown to rely on XPO1 to be shuttled into the cytoplasm for its antiapoptotic function (23). While expression of survivin has been shown to be regulated by nuclear factor kappa-light-chain-enhancer of activated B cells (NFkB) in breast cancer (24), activated NFkB pathway has also been shown to contribute to malignant progression of adult T-cell leukemia (ATL) through survivin (25).…”
Section: Introductionmentioning
confidence: 99%